Economic Development Strategy: An Analysis of Leading Sector in Disadvantaged Regions of Pesisir Barat Regency - Feri Hardani; Toto Gunarto; Neli Aida; Yudastio Yudastio (Journal Corner of Education, Linguistics, and Literature, 2021)
Pesisir Barat Regency is the youngest regency in Lampung Province. Pesisir Barat Regency is the result of the division of West Lampung Regency, which was ratified based on Law Number 22 of 2012 concerning the Establishment of the West Coast Regency of Lampung Province on October 25, 2012 then inaugurated on April 22, 2013. West as an underdeveloped district in Indonesia, As a new autonomous region, West Coast District continues to improve to catch up, align itself or even surpass other areas in Lampung Province. Efforts to improve are carried out in a synergistic and simultaneous manner covering all fields and sectors, both in the government, economic, and cultural sectors. These efforts lead to the goal of prospering the people of Pesisir Barat Regency. West coast district has a lot of regional potential that can be developed to improve the status of the area and carry out development for progress. This study aims to look at the leading sectors in the disadvantaged areas of the west coast district. Based on the results of the analysis and calculation results that have been carried out, there are several leading sectors in the west coast district, namely the Location Question> 1. Shortly, the west coast district as a disadvantaged district has the potential to be developed based on its superior sector.